GAMBARAN KADAR ALBUMIN DARAH PADA USIA LANJUT YANG TINGGAL DI JALAN BUNG LORONG 10 KECAMATAN TAMALANREA MAKASSAR - Jurnal Syarif; Andi Indrawati; Marselina Marselina (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2019)
Albumin is the highest plasma protein in the amount of around 60% and has various functions that are very important for health, namely the formation of new cell tissue, accelerating the recovery of damaged body tissue and maintaining fluid balance in blood vessels with fluid in the interstitial cavity within the limits normal. At an advanced age, albumin levels do not increase if there is an increase in the patient's history, and also heredity. This type of research is a descriptive laboratory observation, which is to determine the description of blood albumin levels in the elderly. The purpose of this study was to determine the description of blood albumin levels in old age. Based on statistical analysis and the average value known to the results of examination of blood albumin levels in old age using a 5010 photometer an average value of 4.15 g / dl. This value indicates that the average patient over 60 years has normal albumin levels. It can be concluded that blood albumin levels in the elderly as many as 20 samples obtained results in 100% normal albumin levels. The suggestions from this study provide knowledge to the public about albumin examination, and further research is carried out with a larger sample quantity to get a more accurate examination of albumin levels.